(untitled) (IAHS Medical Journal, 2024)
Background: The care of critically ill children remains one of the most demanding and challenging aspects in the field of pediatrics. Pediatric Intensive Care Unit (PICU) aims at promoting early intervention and quality care for achieving good results and better prognosis. With the advancement in intensive care facilities, there is a dramatic increase in survival of critically ill children. It is usually offered to patients whose condition is potentially reversible and who have a good chance of surviving with intensive care support. Since these patients are critically ill, the outcome of intervention is sometimes difficult to predict. This study is aimed to assess the clinical profile of critically ill children presenting to the pediatric emergency room and then their admission pattern to the pediatric intensive care unit. This may help to assist intensivist and planners to pay due attention for better utilization of healthcare facilities. Better understanding leads to better management. Materials and methods: This is a cross-sectional study, conducted at the Pediatric Intensive Care Unit of Chattagram Maa Shishu-O-General Hospital from January to June of 2019. A total of 100 admitted cases were recruited and their symptoms and signs, clinical findings and diagnosis were recorded accordingly. All the patients were aged within 28 days to below 14 years. Results: Among the 100 study subjects, 66 were male and 34 were female. The mean age was 1.73 ± 2.6 years. Most children were admitted with respiratory distress though there were other accompanying signs and symptoms. The symptoms subjects commonly presented with were respiratory distress(76%), tachycardia(70%), lung crepitations (69%), tachypnea (68%), fever (67%), lethargy (59%), feeding difficulty (59%), convulsions (48%), low blood pressure (24%), hepatomegaly (19%), cyanosis (14%), edema (6%), congenital anomalies (4%). The clinical findings that led them to PICU admissions were bronchiolitis (4%), bronchopneumonia (42%), respiratory failure of any cause (4%), heart failure (7%), cyanotic congenital heart disease (8%), acyanoticcongenital heart disease (7%), meningitis (13%), encephalitis (12%), cerebral palsy with seizure disorder (21%), status epilepticus (2%), Gullein Barre Syndrome (3%), hyponatremic dehydration (6%), acute kidney injury (2%), acute leukemia (2%).In this study, neurological disorders such as cerebral palsy with seizure disorder and encephalitis and meningitis were among the top five in the diagnosis list. Septicemia with shock was also a very common finding promoting admission to PICU. GCS was found to be significantly lower in the above-mentioned disease conditions making admission to the ICU quite plausible. Conclusion: Children admitted to PICU may have multiple clinical findings and disease patterns. However, some diseases predominate the patient population admitted to PICU.The knowledge of clinical spectrum and epidemiological profile of critically ill children plays a significant role in the planning of health policies that would mitigate various factors related to the evolution of diseases prevalent in these sectors. Descriptive epidemiology focuses on identifying and reporting the pattern and frequency of events related to the health of a population. IAHS Medical Journal Vol 7(1), June 2024; 44-49